Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To solve the equation [tex]\((x-4)^2 + 4 = 49\)[/tex], let's go through the solution step-by-step:
1. Simplify the equation:
Start by rewriting the given equation:
[tex]\[ (x-4)^2 + 4 = 49 \][/tex]
2. Isolate [tex]\((x-4)^2\)[/tex]:
Subtract 4 from both sides to isolate the squared term:
[tex]\[ (x-4)^2 + 4 - 4 = 49 - 4 \][/tex]
[tex]\[ (x-4)^2 = 45 \][/tex]
3. Solve for [tex]\(x-4\)[/tex]:
To solve for [tex]\(x-4\)[/tex], take the square root of both sides:
[tex]\[ \sqrt{(x-4)^2} = \sqrt{45} \][/tex]
Remember that taking the square root gives both positive and negative solutions:
[tex]\[ x-4 = \pm \sqrt{45} \][/tex]
4. Simplify [tex]\(\sqrt{45}\)[/tex]:
Note that [tex]\(\sqrt{45}\)[/tex] can be simplified:
[tex]\[ \sqrt{45} = \sqrt{9 \times 5} = \sqrt{9} \times \sqrt{5} = 3\sqrt{5} \][/tex]
Therefore, we have:
[tex]\[ x-4 = \pm 3\sqrt{5} \][/tex]
5. Solve for [tex]\(x\)[/tex]:
Isolate [tex]\(x\)[/tex] by adding 4 to both sides:
[tex]\[ x = 4 \pm 3\sqrt{5} \][/tex]
6. Conclude the solutions:
The solutions to the equation [tex]\((x-4)^2 + 4 = 49\)[/tex] are:
[tex]\[ x = 4 - 3\sqrt{5} \quad \text{and} \quad x = 4 + 3\sqrt{5} \][/tex]
Hence, the solutions are:
[tex]\[ x = 4 - 3\sqrt{5} \quad \text{and} \quad x = 4 + 3\sqrt{5} \][/tex]
None of the other options provided ([tex]\(x= -4 \pm 2 \sqrt{10}\)[/tex], [tex]\(x= \pm 7\)[/tex], [tex]\(x=-4 + \sqrt{45}\)[/tex]) match our found solutions. The correct solution is indeed:
[tex]\[ x = 4 - 3\sqrt{5} \quad \text{and} \quad x = 4 + 3\sqrt{5} \][/tex]
1. Simplify the equation:
Start by rewriting the given equation:
[tex]\[ (x-4)^2 + 4 = 49 \][/tex]
2. Isolate [tex]\((x-4)^2\)[/tex]:
Subtract 4 from both sides to isolate the squared term:
[tex]\[ (x-4)^2 + 4 - 4 = 49 - 4 \][/tex]
[tex]\[ (x-4)^2 = 45 \][/tex]
3. Solve for [tex]\(x-4\)[/tex]:
To solve for [tex]\(x-4\)[/tex], take the square root of both sides:
[tex]\[ \sqrt{(x-4)^2} = \sqrt{45} \][/tex]
Remember that taking the square root gives both positive and negative solutions:
[tex]\[ x-4 = \pm \sqrt{45} \][/tex]
4. Simplify [tex]\(\sqrt{45}\)[/tex]:
Note that [tex]\(\sqrt{45}\)[/tex] can be simplified:
[tex]\[ \sqrt{45} = \sqrt{9 \times 5} = \sqrt{9} \times \sqrt{5} = 3\sqrt{5} \][/tex]
Therefore, we have:
[tex]\[ x-4 = \pm 3\sqrt{5} \][/tex]
5. Solve for [tex]\(x\)[/tex]:
Isolate [tex]\(x\)[/tex] by adding 4 to both sides:
[tex]\[ x = 4 \pm 3\sqrt{5} \][/tex]
6. Conclude the solutions:
The solutions to the equation [tex]\((x-4)^2 + 4 = 49\)[/tex] are:
[tex]\[ x = 4 - 3\sqrt{5} \quad \text{and} \quad x = 4 + 3\sqrt{5} \][/tex]
Hence, the solutions are:
[tex]\[ x = 4 - 3\sqrt{5} \quad \text{and} \quad x = 4 + 3\sqrt{5} \][/tex]
None of the other options provided ([tex]\(x= -4 \pm 2 \sqrt{10}\)[/tex], [tex]\(x= \pm 7\)[/tex], [tex]\(x=-4 + \sqrt{45}\)[/tex]) match our found solutions. The correct solution is indeed:
[tex]\[ x = 4 - 3\sqrt{5} \quad \text{and} \quad x = 4 + 3\sqrt{5} \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.